Operational safety evaluation of tanker cargo oil system fusing multiple task information. (1st November 2021) - Wang, Chunping; Fan, Shidong; Yao, Yunan; Wu, Jie; Wang, Bin; Zheng, Liangyan
Abstract: The cargo oil system is an irreplaceable component of a tanker, of which the operational safety affects task completion. This study proposes an operational safety evaluation methodology for fusing multiple task information, which identifies the assessment level and abnormal points. Different data features are used to express the changes in the operating state at different time stages. To improve the performance of the method, the data monitoring error analysis technique based on distance and coefficient of variation approach are employed to deal with uncertainty and subjectivity. The optimal data reliability and comprehensive weight are then fed as input values to the Evidential Reasoning(ER) rule. The proposed operational safety evaluation methodology has been applied to the cargo pump system of a 49, 000-ton tanker. Comparing with equipment maintenance records, the results of the proposed method can reflect the actual task safety condition and verify the feasibility and effectiveness. Furthermore, weak links and improvement measures present new insights for operational safety management for tanker corporations. Highlights: A methodology for fusing multiple task information to evaluate the operational safety of cargo oil system is proposed. The rule-based method converts the input information in different formats into a uniform belief degree distribution. The data reliability and weight simultaneously of evaluation indexes are considered simultaneously. A case study on the operation safety of a 49, 000-ton oil tanker cargo pump system is conducted.